2015
DOI: 10.3329/bjb.v43i3.21606
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and acetylcholinesterase activities of three species of the family Lamiaceae

Abstract: Antioxidant and acetylcholinesterase inhibitory activity of the three species namely, Endostemon obtusifolius (E. Mey. ex benth.) N. E. Br, Plectranthus zuluensis (T. Cooke) and Tetradenia riparia (Hochst.) Codd. were evaluated. Maximum antioxidant activity was exhibited by E. obtusifolius (IC50 130 ?g/ml) followed by T. riparia (IC50 142 ?g/ml) and P. zuluensis (IC50 169 ?g/ml). Acetylcholinesterase inhibition (AChEI) was highest in P. zuluensis (IC50 290 ?g/ml) followed by E. obtusifolius (IC50 470 ?g/ml) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…is a relatively unknown and under-explored member of the mint family that grows in semi-arid regions of southern Africa. Its pharmacological activities have not been verified, although it has free radical-scavenging and acetylcholinesterase-inhibiting properties [ 22 ]. The endophytic composition of its organs, its drought tolerance capability, and the plant growth-promoting properties of the endophytes have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…is a relatively unknown and under-explored member of the mint family that grows in semi-arid regions of southern Africa. Its pharmacological activities have not been verified, although it has free radical-scavenging and acetylcholinesterase-inhibiting properties [ 22 ]. The endophytic composition of its organs, its drought tolerance capability, and the plant growth-promoting properties of the endophytes have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…16 The total phenolic contents of the examined plant extracts are presented in Table 1. In this experiment, the highest phenolic content was found P. vestitus (2.8/100 g), followed by P. mollis (2.5/100 g) and P. speciosus (2.3/100 g).…”
Section: Total Phenols and Total Flavonoidsmentioning
confidence: 99%
“…Accordingly, Uddin et al [38] and Boonsong et al [47] reported the fact that polyphenols attributed to both antioxidant and AChE inhibitory activity significantly. In fact, polyphenolic compounds such as gallotannins, condensed tannins and flavonoids contribute directly to the antioxidant activity and AChE inhibitory activity of plant extracts [48]. The total polyphenol and total flavonoid contents were moderately correlated with the AChE inhibitory activity however, the degree of correlation was lower than that in the correlation observed with the total antioxidant activity by four assays.…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, the extracts containing non-polar phytochemicals such as alkaloids might be responsible for high inhibitory activity particularly on AChE. In fact, the alkaloids are the main secondary metabolites which are of concern in the synthesis of novel anticholinesterase drugs rather than polyphenolic/flavonoid compounds [48,51,52].…”
Section: Resultsmentioning
confidence: 99%